Finanse bibliotek uniwersyteckich w Polsce - Problemy i propozycje - Jazdon, Artur (My University, 2000)
The author turns the attention to the lack of an institution that could make proposals and decisions about funding of academic libraries. Simultaneously, there are no standards of libraiy performance for the purpose of library evaluation. Current scheme of university financing with the funds divided into departments complicates the problem of overall costs including central libraiy funding. Another disadvantages of the situation of the central university libraries include their organisational placement and rules of financing. The author proposes initiating of the state programs supporting particular projects and tasks, modifications of the policies of the Scientific Research Committee (KBN), more active search of funding (including KBN grants) and cost reductions in libraries.
FINANCES OF UNIVERSITY LIBRARIES IN POLAND. PROBLEMS AND PROPOSALS